The Role of PIEZO2 in Human Mechanosensation - Chesler, Alexander T; Szczot, Marcin; Bharucha-Goebel, Diana; Čeko, Marta; Donkervoort, Sandra; Laubacher, Claire; Hayes, Leslie H; Alter, Katharine; Zampieri, Cristiane; Stanley, Christopher; Innes, A. Micheil; Mah, Jean K; et al. (The New England journal of medicine, 2016)
Inactivating variants in PIEZO2, which encodes a stretch-gated ion channel, impair touch perception and proprioception. Visual cues partially compensate for these impairments, allowing affected persons to perform complex movements with greater accuracy. The ability to sense force, which is known as mechanosensation, provides humans and other animals with important information about the environment; it is crucial for social interactions, such as comforting or caressing, and is required for motor coordination. A number of anatomical classes of somatosensory neurons with distinct selectivity for mechanical stimuli have been identified, but the way in which these inputs combine to provide the richness of the human sense of touch remains unclear. 1 , 2 Similarly, proprioception is considered to be essential for posture and controlled movement, but little is known about the underlying mechanisms and the precise role . . .